Sperm-Mediated Transgenerational Inheritance - Spadafora, Corrado (Frontiers in Microbiology, 2017)
Spermatozoa of virtually all species can spontaneously take up exogenous DNA or RNA molecules and internalize them into nuclei. In this article I review evidence for a key role of a reverse transcriptase (RT) activity, encoded by LINE-1 retrotransposons, in the fate of the internalized nucleic acid molecules and their implication in transgenerational inheritance. LINE-1-derived RT, present in sperm heads, can reverse-transcribe the internalized molecules in cDNA copies: exogenous RNA is reverse-transcribed in a one-step reaction, whereas DNA is first transcribed into RNA and subsequently reverse-transcribed. Both RNA and cDNA molecules can be delivered from sperm cells to oocytes at fertilization, further propagated throughout embryogenesis and inherited in a non-Mendelian fashion in tissues of adult animals. The reverse-transcribed sequences are extrachromosomal, low-abundance, and mosaic distributed in tissues of adult individuals, where they are variably expressed. These "retrogenes" are transcriptionally competent and induce novel phenotypic traits in animals. Growing evidence indicate that cancer tissues produce DNA- and RNA-containing exosomes. We recently found that these exosomes are released in the bloodstream and eventually taken up into epididymal spermatozoa, consistent with the emerging view that a transgenerational flow of extrachromosomal RNA connects soma to germline and, further, to next generation embryos. Spermatozoa play a crucial bridging role in this process: they act as collectors of somatic information and as delivering vectors to the next generation. On the whole, this phenomenon is compatible with a Lamarckian-type view and closely resembles Darwinian pangenesis.